Integration of X-ray absorption fine structure databases for data-driven materials science. Issue 1 (31st December 2023) - Ishii, Masashi; Tanabe, Kosuke; Matsuda, Asahiko; Ofuchi, Hironori; Matsumoto, Takahiro; Yaji, Toyonari; Inada, Yasuhiro; Nitani, Hiroaki; Kimura, Masao; Asakura, Kiyotaka
ABSTRACT: With the aim of introducing data-driven science and establishing an infrastructure for making X-ray absorption fine structure (XAFS) spectra findable and reusable, we have integrated XAFS databases in Japan. This integrated database (MDR XAFS DB) enables cross searching of spectra from more than 2000 samples and more than 700 unique materials with machine-readable metadata. The introduction of a materials dictionary with approximately 6000 synonyms has improved the search performance and links with large external databases have been established. In order to compare spectra in the database, the energy calibration policies of each institution were compiled, and the energy calibration methods across institutions were shown. This clarified how to utilize the MDR XAFS DB as a knowledge base. The database created through this cross-institution initiative is a model case for the further development of databases for other methods and material informatics using them. GRAPHICAL ABSTRACT: uf0001